Association of an organ transplant-based approach with a dramatic reduction in postoperative complications following radical nephrectomy and tumor thrombectomy in renal cell carcinoma. Issue 10 (October 2019) - González, Javier; Gaynor, Jeffrey J.; Martínez-Salamanca, Juan I.; Capitanio, Umberto; Tilki, Derya; Carballido, Joaquín A.; Chantada, Venancio; Daneshmand, Siamak; Evans, Christopher P.; Gasch, Claudia; Gontero, Paolo; Haferkamp, Axel; et al.
Abstract: Objectives: Our aim was to determine whether using an organ transplant-based(TB) approach reduces postoperative complications(PCs) following radical nephrectomy(RN) and tumor thrombectomy(TT) in renal cell carcinoma(RCC) patients with level II-IV thrombi. Methods: A total of 390(292 non-TB/98 TB) IRCC-VT Consortium patients who received no preoperative embolization/IVC filter were included. Stepwise linear/logistic regression analyses were performed to determine significant multivariable predictors of intraoperative estimated blood loss(IEBL), number blood transfusions received, and overall/major PC development within 30days following surgery. Propensity to receive the TB approach was controlled. Results: The TB approach was clearly superior in limiting IEBL, blood transfusions, and PC development, even after controlling for other significant prognosticators/propensity score(P < .000001 in each case). Median IEBL for non-TB/TB approaches was 1000 cc/300 cc and 1500 cc/500 cc for tumor thrombus Level II-III patients, respectively, with no notable differences for Level IV patients(2000 cc each). In comparing PC outcomes between non-TB/TB patients with a non-Right-Atrium Cranial Limit, the observed percentage developing a: i) PC was 65.8%(133/202) vs. 4.3%(3/69) for ECOG Performance Status(ECOG-PS) 0–1, and 84.8%(28/33) vs. 25.0%(4/16) for ECOG-PS 2–4, and ii) major PC was 16.8%(34/202) vs. 1.4%(1/69) for ECOG-PS 0–1, and 27.3%(9/33) vs. 12.5%(2/16) for ECOG-PS 2–4. Major study limitation was the fact that all TB patients were treated by a single, experienced, high volume surgeon from one center (non-TB patients were treated by various surgeons at 13 other centers). Conclusions: Despite this major study limitation, the observed dramatic differences in PC outcomes suggest that the TB approach offers a major breakthrough in limiting operative morbidity in RCC patients receiving RN and TT.